CORRELATION BETWEEN OVERALL SLOPE AND SLOPE STABILITY OF HIGHWALL IN PIT TUNGGAL, BORNEO - MANIK, VITO ARISTO; NINGRUM, WIWIN JUNITA; KHOIRULLAH, NUR; SOPHIAN, RADEN IRVAN; ZAKARIA, ZUFIALDI (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
Slope stability is an important aspect of the mining operation. Hence, an in-depth understanding of slope stability and variable that affect it is very crucial. This research was conducted in pit tunggal, Borneo. The aim of this research is to identify the correlation between overall slope and slope stability in highwall slope at pit tunggal. Slope stability analysis was conducted with SLIDE V 6.00 software using Morgenstern-Price’s limit equilibrium method. The result of this research shows that, as the highwall slope gets steeper, the slope stability represented by a factor of safety (FS) may decrease. Otherwise, when the highwall slope gets declivous, the factor of safety may increase.